(untitled) (African Journal of Biomedical Research, 2022)
Background: Suprascapular notch (SSN) of the scapular is a depression on the lateral part of its superior border, which is bridged by the superior transverse scapular ligament as it transmits the suprascapular nerve to the supraspinous fossa. Variations in morphology of the SSN have been associated with suprascapular nerve entrapment. Aim: The aim of this study was to characterize the morphological variations of suprascapular notch in Nigerian dry scapulae. Methods: A total of 193 human dry scapulae (96 Right and 97 Left) were studied. The variables of study included the shape of the SSN, superior transverse diameter (STD), inferior transverse diameter (ITD) and maximum depth (MD) of the SSN. The metric variables were measured with a Vernier Calliper. The SSN was classified based on Renganchary et al classification. Results: The values of the STD, ITD, and MD were 1.285 ± 0.536, 0.724 ± 0.316 and 0.997 ± 0.441 respectively. These values showed no statistical difference between the right and the left sides. The prevalence of the types of SSN (in decreasing order) were type III (71%), type II (22%), type I & V (3% each) type IV (1%) and type VI (0%). Conclusion: The findings of the present study showed that type III was the most prevalent type while type VI (formed by complete ossification of the suprascapular ligament) was not found in the study.